Pemetaan Penelitian Resiliensi Organisasi pada Pendidikan Tinggi: Sebuah Analisis Bibliometrik - Mulya, Diki Akhwan; Sumertajaya, I Made; Sukmawati, Anggraini (Jurnal Manajemen dan Organisasi, 2025)
Organizations are confronted with multiple uncertainties and unexpected changes, requiring them to survive and adapt in order to achieve long-term success. One strategic approach that has increasingly attracted scholarly attention is the strengthening of organizational resilienceNevertheless, academic studies on organizational resilience within the higher education sector continue to exhibit diverse developmental patterns and therefore require comprehensive mapping. This study adopts a bibliometric approach using data retrieved from the Scopus database. Articles were collected using the keyword string “organizational_resilience_AND_higher_education” within the subject areas of business, management, and accounting. All data were analyzed using VOSviewer software to map publication trends, author networks, institutional affiliations, and keyword interrelationships. The results reveal that the highest number of publications occurred in 2021, with a total of 50 articles. The most productive institutional affiliation was Technische Universität Dresden, with five publications. Furthermore, keywords with the highest total link strength included industry, COVID, organizational resilience, and technology. Author network analysis identified 14 interconnected authors within collaborative research clusters. These findings indicate a growing academic focus on organizational resilience in the higher education sector, particularly in response to global challenges such as the COVID-19 pandemic and technological transformation.